2020
DOI: 10.1038/s41598-020-67501-9
|View full text |Cite
|
Sign up to set email alerts
|

Segmental aneuploidies in fetuses with isolated echogenic intracardiac focus among women younger than 35 years

Abstract: Studies on the occurrence of segmental aneuploidoidy in fetuses with isolated echogenic intracardiac focus (eif) are scarce. the aim of this study was to analyze whether there is an association between abnormal segmental aneuploidies and isolated eif. this was a prospective case-control study. the study participants in the case group were fetuses that were diagnosed with isolated eif. Samples without fetal ultrasound abnormalities but received prenatal diagnosis for other reasons (serological screening high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Three studies also reported abnormalities among those without EIF and in each of these studies the internal comparison of abnormality rate between EIF and non-EIF suggested no higher rate of chromosomal abnormalities among those with EIF ( Fig 4 ). The sample size of EIF pregnancies were 58 in Ko et al [ 22 ], 1099 in Wang et al [ 18 ] and 230 in Mirza et al [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies also reported abnormalities among those without EIF and in each of these studies the internal comparison of abnormality rate between EIF and non-EIF suggested no higher rate of chromosomal abnormalities among those with EIF ( Fig 4 ). The sample size of EIF pregnancies were 58 in Ko et al [ 22 ], 1099 in Wang et al [ 18 ] and 230 in Mirza et al [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has described EIF as often transient, resolving by the third trimester of pregnancy or after delivery [ 18 ], nonpathological or benign in isolation [ 11 ], and therefore has been highlighted that isolated soft markers may be present in 10% of normal foetuses [ 19 ]. However, multiple USM and the presence of specific soft markers, in terms of the specific location and size, may be associated with underlying chromosomal abnormalities (such as an association between the presence of EIF and a later diagnosis of Down’s syndrome) albeit the current evidence is not supportive of this [ 20 ] or adverse infant outcomes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 However, contemporary research has indicated that isolated EICF does not increase the risk of aneuploidy. 20 The Society for Maternal-Fetal Medicine (SMFM) 21 advocates for NIPT as a prudent choice for cases of EICF, particularly in instances where aneuploidy screening has not been performed previously. Li S et al 22 suggest that when NIPT results are negative, EICF should be considered a normal variant.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the population included in our study was predominantly young (below the age of 35 years at the expected date of con nement), while there were 9.37% pregnant women of an advanced maternal age in previous studies [12]. According to the relevant regulations (Article 20 of the Measures for the Implementation of Law of the Peoples Republic of China on Maternal and Infant Health Care (promulgated on June 20, 2001) ), prenatal diagnosis is often recommended for pregnant women in China who are at high risk based on maternal serum screening [20,21], advanced maternal age and fetuses with structural abnormalities, therefore, the risk of potential chromosomal aberrations was higher in those studies [12,19]. In addition, the proportion of various types of USM in the study population was also different; EIF accounted for 23.72% in a previous study [12], whereas in our study, EIF was the most frequent USM (81.71%).…”
Section: Discussionmentioning
confidence: 99%